THE EFFETIVENESS OF USING TWO STAY TWO STRAY TECHNIQUE TO TEACH READING COMPREHENSION ON FACTUAL REPORT TEXT AT TENTH GRADE STUDENTS OF MAN 4 KEDIRI - M. Syaichul Muchyidin; Ange Rias Jiwani (STKIP PGRI Jombang, 2020)
Reading comprehension is an important part of reading process. In learning English, students may face some difficulties in learning reading, even though they are students of Senior High School. Therefore, the teacher should teach them by appropriate technique to solve their difficulties. This study is aimed to investigate the effectiveness of using Two Stay Two Stray Techniques to teach reading comprehension on factual report text. The research design used is a static group comparison design of pre-experimental design. The study is conducted by applying Two Stay Two Stray (TS-TS) technique to the experimental class only. There are 34 students in experimental class and 34 students in control class. The result of data analysis shows that the mean score of post-test for experimental class is 81.06 while the post-test of control class is 71.88. It can be seen that the experimental class outperformed the control class in reading comprehension with t = 2.028, df = 66 and P = .005 and 95% confidence interval ranging from 143 to 18.210. The result of t-test shows that the mean difference is 9.176 with sig. (2-tailed) value 0.047. It can be seen that the value 0.047 is lower than 5% (0.047 < 0.05). It can be concluded that the t-value is significant in 5% significant level. It means that there is significant difference between control and experimental class. Thus, there is a significant effect of using Two Stay Two Stray technique to teach reading comprehension at tenth grade students of MAN 4 Kediri. It can be seen from the sig (2-tailed). Therefore, the effectiveness of using Two Stay Two Stray technique to teach reading comprehension is an effective way to increase the students’ ability.